Enterobacter cloacae ulceration in a failed corneal graft: a case report. - Gross, N D (1985)
A 70-year-old female developed a bacterial ulcer in a previously rejected corneal graft. Cultures identified the pathogen as Enterobacter cloacae. Intensive topical antibiotic therapy arrested the progress of the ulcer, and the epithelial defect healed in one week; there was no resultant stromal thinning. Factors which may have predisposed the cornea to ulceration by this organism of relatively low virulence include chronic oedema following graft rejection, topical corticosteroid therapy, and tear insufficiency.